Creativity development through questioning activity in second language education - Yu, Xiaoling; Wang, Tzu-Yang; Yuizono, Takaya (Frontiers in Education, 2023)
Creativity is an important 21st-century skill that also plays an important role in second language use and development. This study examined the effects of creative pedagogy on student questioning activities for second language learners' creativity, language proficiency, and questioning ability. In the Japanese second language course, a creative activity intervention with questioning activities was conducted for 81 university students. The students were taught how to ask higher-order questions, and they performed questioning activities and discussions about their questions after reading articles for eight lectures in four weeks. The results demonstrated that creative pedagogy significantly improved learners' creativity, second language performance, and questioning ability, with a particularly positive impact on questioning ability, representing innovative thinking skills. The findings of this study not only contribute to future research on the development of creativity in second language instruction and deepen the exploration of the development of questioning ability for innovative thinking skills.